Analysis of seismic bidirectionality on response of reinforced concrete structures with irregularities of l-shaped plan and soft story - Sobrado, V. H. (2020)
The seismic design of buildings is usually performed using one-way analysis for each of main axes independently. However, seismic events have fairly random behaviour and impose bidirectional solicitations on structures. In this work, the study of the response in structures subjects to earthquake loads with irregularity of l-shaped plan and soft story is carried out. For this, the linear time-story analysis (LTHA) of these has been carried out imposing seismic solicitations in two orthogonal directions. Thus, the structural response with incidence angle variations of 10 is obtained and compared with the response derived from the unidirectional analysis. Variations of up to 50% and 72% are obtained for model structures with l-shaped plan and soft story respectively.